2021 ACM/IEEE International Conference on Model Driven Engineering Languages and Systems Companion (MODELS-C) 2021
DOI: 10.1109/models-c53483.2021.00011
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Collaborative Modeling across Language Workbenches – a Case on Jetbrains MPS and Eclipse Spoofax

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This step is crucial since it is not possible to simply forward the edit operations performed on one modeling environment to all the other modeling environments. As we learned in our previous work [33], this is true even if the concrete syntax of the modeling environments is the same. Edit adaptations can act also as a filter, for example, we expect that several changes performed in graphical models might not need to be forwarded to textual modeling environments.…”
Section: ) Edit Adaptationmentioning
confidence: 76%
See 1 more Smart Citation
“…This step is crucial since it is not possible to simply forward the edit operations performed on one modeling environment to all the other modeling environments. As we learned in our previous work [33], this is true even if the concrete syntax of the modeling environments is the same. Edit adaptations can act also as a filter, for example, we expect that several changes performed in graphical models might not need to be forwarded to textual modeling environments.…”
Section: ) Edit Adaptationmentioning
confidence: 76%
“…In our previous work, we presented a language dependent tool, Parsafix, which enables real-time collaboration among engineers working on Modelix and Saros [33]. Modelix is a real-time collaboration tool for JetBrains MPS, and Saros is a real-time collaboration tool for the Eclipse IDE (as well as IntelliJ).…”
Section: Related Workmentioning
confidence: 99%
“…A few months later, the first author also joined on the Spoofax implementation and both first and second authors have been maintaining this implementation ever since. During this time, the third author was involved in the design decisions for the Spoofax implementation and some master students have contributed as well [46][47][48].…”
Section: Contextmentioning
confidence: 99%
“…Real-time collaboration has been identified as the main trending topic in previous studies (David et al, 2021a;Franzago et al, 2018), aligning well with its 95% industry need. Especially driven by relaxed consistency models (such as eventual consistency (Vogels, 2009) and strong eventual consistency (Preguiça et al, 2009)), the feasibility of real-time collaborative modeling has been demonstrated in conceptual modeling (Nicolaescu et al, 2018), requirements modeling (Saini and Mussbacher, 2021), cross-platform collaborative modeling (Voogd et al, 2021), and collaborative multi-level modeling (David and Syriani, 2022). A combination of Real-time collaboration and traditional Versioning (Git) has been recently implemented in WebGME (Maróti et al, 2014b).…”
Section: Collaborationmentioning
confidence: 99%